2004
DOI: 10.1093/hmg/ddh132
|View full text |Cite
|
Sign up to set email alerts
|

Data mining and multiparameter analysis of lung surfactant protein genes in bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD), the most common chronic lung disease in infancy, is influenced by a number of antenatal and postnatal risk factors and is mostly preceded by respiratory distress syndrome (RDS) in the newborn. Surfactant protein (SP-A, -B, -C and -D) gene variations may play a role in both BPD and RDS. An association study between these candidate genes and BPD was performed. A total of 365 preterm Finnish infants in a high-risk population with gestational age Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 40 publications
5
45
0
1
Order By: Relevance
“…Some of the studies that reported gene polymorphisms associated with BPD did not evaluate the independency from O 2 exposure (10,13,14), making it rather difficult to evaluate the interaction of the associated polymorphisms with the main environmental causative factor of BPD. Interestingly, a recent report showed that a promoter polymorphism (Ϫ460 T/C) of the VEGF gene was associated with an increased risk of BPD, independently from the duration of O 2 exposure (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies that reported gene polymorphisms associated with BPD did not evaluate the independency from O 2 exposure (10,13,14), making it rather difficult to evaluate the interaction of the associated polymorphisms with the main environmental causative factor of BPD. Interestingly, a recent report showed that a promoter polymorphism (Ϫ460 T/C) of the VEGF gene was associated with an increased risk of BPD, independently from the duration of O 2 exposure (12).…”
Section: Discussionmentioning
confidence: 99%
“…interleukin-6 or 13), or deficiency in Toll-like receptor 4, which is a critical receptor component for gram-negative bacteria's lipopolysaccharide inflammatory response, show increased susceptibility to hyperoxia-induced lung injury. [19][20][21][22][23] In humans, polymorphisms in surfactant protein A & B, TNF-α, angiotensin-converting enzyme and gluthathione-S-transferase-P1 genes, genes, and having known altered biological functions, have been linked in small studies with variations in risk of BPD or its severity, [24][25][26][27] although others have failed to show similar associations in independent populations. 28,29 PDA persistence was also largely heritable in our analysis, a finding that is consistent with a significant contribution of individual's ethnic background to susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the functional relationship of MBL and other humoral lectins as SP-D and SP-A in the pulmonary innate host defense may reveal new aspects in the pathogenesis of the disease that need to be focussed in further studies. 43,44 Furthermore, the results of this study need to be validated in further independent samples. The fact that no association between the development of early-onset or nosocomial infections and the MBL polymorphisms investigated was detected can be explained by the severe immaturity of the immune system in the preterm infants.…”
Section: Discussionmentioning
confidence: 96%